Procurement organisation in project-based setting: a multiple case study of engineer-to-order companies. Issue 9 (27th July 2022) - Moretto, Antonella; Patrucco, Andrea Stefano; Walker, Helen; Ronchi, Stefano
Abstract: Procurement decisions have a pervasive impact on supply chain performance and market success. This is particularly true in supply chains operating to deliver projects, such as construction and engineer-to-order companies, where a focal firm's procurement decisions need to be coordinated with production activities to effectively satisfy customer orders. This study focuses on how the procurement department can be organised in order to support the needs of project-based supply chains better. Starting from a review of the procurement organisation literature in the context of project supply chains, we use a multiple case study methodology and discuss the procurement organisational choices in 11 project-based companies. Within and cross-case analyses allow identifying two possible archetypes, i.e. the procurement—focussed and the project-focussed organisations, as extremes on a continuum that also includes hybrid solutions. The characteristics of each model are discussed, and results are articulated in three propositions connecting procurement organisational variables and contingent factors.